Outcomes of children with biopsy-proven Langerhans cell histiocytosis (LCH) treated at the Red Cross War Memorial Children's Hospital from 1998 – 2017 - Hlatywayo, Loyce (Department of Paediatrics and Child Health, 2025)
Background: Langerhans Cell Histiocytosis (LCH) is a rare histiocytic disorder characterised by the infiltration of a single organ or multiple organs by cells phenotypically similar to Langerhans cells. The number and type of systems involved affect the outcome and the longer the maintenance chemotherapy the longer the periods of remission. a. Rationale: This study evaluated the demographic data of our patient population, the course of disease and the outcomes of treatment in children who had LCH at Red Cross War Memorial Children's Hospital (RCWMCH) from 1998 to 2017. Methods: A retrospective document review of all children diagnosed with LCH at RCWMCH between 1 January 1998 and 31 December 2017. Data was collected from patient folders and entered into Microsoft access database. Data was transferred and analysed in StatisticaTM. Where two groups were compared, using the log rank test, a p value of 0.05 was regarded as significant. Results: There were 30 patients between the ages of 1 month and 12 years (median 2 years). The male to female ratio was 1:1.5. Seventeen patients (56.7%) presented with multisystem disease with risk organ involvement (MS RO LCH). Twelve patients (40%) had single system LCH (SS LCH) and only one patient had multisystem disease with no risk organ involvement. The patients were treated with modified versions of serial Histiocyte Society LCH II -IV protocols. Overall mortality of the whole group was 16.7% with a 5-year overall survival (OS) of 83% and a 5-year event free survival (EFS) of 58%. SS-LCH patients fared better with 5-year OS of 100% and EFS of 90%. Considering the whole group, the 5-year OS was lower in patients < 1 year of age (44 % versus 100 % in children >1 year of age (p=0.002), as was EFS (15% versus 77%) (p =0.008). Discussion: Our patient demographic differed from published data with respect to younger age at presentation and female predominance. The majority of our patients presented with MS RO LCH which is not consistent with published data. The 5-year OS was slightly lower than the 5- year OS published in high income countries. These differences could be explained by the exclusion of adolescents and young adults from our cohort. Conclusion: Patients with MS RO LCH had a poorer outcome despite more intensive therapy. The 5-year OS and EFS were consistently lower in those patients less than 1 year of age at diagnosis.